The Impact of Pesticide Exposure on Farmers' Respiratory Health: An Agronursing Perspective - Vanessa Octavia Ramadhani; Kanaya Nugita; Dinda Wahyu Dinanti; Enggal Hadi Kurniyawan; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi; Dicky Endrian Kurniawan (KHD Production, 2025)
Pesticide exposure is one of the most significant risks farmers faces, especially regarding respiratory health. Lack of understanding about using personal protective equipment (PPE) and safe work procedures makes farmers vulnerable to respiratory problems. This study aims to identify the impact of pesticide exposure on farmers' respiratory health from an agronursing perspective. This research is a literature review study that uses a quantitative descriptive approach. The sample was taken from 10 articles from PubMed, Science Direct, and Semantic Scholar, which were considered most relevant. The study showed pesticide exposure is significantly associated with increased respiratory disorders such as asthma, chronic cough, and decreased lung function. Risk factors include frequency of spraying, type of pesticide, and lack of PPE use. The agronursing approach is important in the prevention and management of health impacts due to pesticides. The role of nurses as educators, behavior change facilitators, and intervention developers is essential to increase farmers' awareness and health protection.